PENDAPATAN DAN DISTRIBUSI PENDAPATAN FUNGSIONAL PETANI PETERNAK SAPI POTONG PADA KELOMPOK WANITA TANI TERNAK "SARI PERTlWI" DAN NON ANGGOTA DI KECAMATAN KUNDURAN, BLORA - Imelda Oct. Utami; Harini Tri Astuti; Mahfutichatun Mahfutichatun (JURNAL LITBANG PROVINSI JAWA TENGAH, 2005)
This research purpose is to analyzed income received by cow breeder and functional income distribution of cow breeder group and non group member. This research is held in Kunduran subdistrict, Blora, from October until December 2003. The sample consists 36 respondents. The sampling method used was stratified random sampling. The location was choosen purposively. The data was analyzed using Hestand partial linear regression and explained descriptively. It was found that total income of farmer group was Rp. 23 I .928,98/per respondent/ per month, while non group was Rp. 318.718, 14/per respondent/ per month. The contribution of input value, compared between farmer group and non group were significant to the total income